Desenvolvimento da habilidade técnica de titulação em um laboratório escolar de química - Terezinha Ribeiro Alvim (2011)
The acquisition of technical skills is one of the main targets of the professionalizing technical courses. This research investigated the learning of the skill of titration in a scholar laboratory of a technological education institution. The goals of this research were: 1- understand how does the evolution of the performance of a student goes in students when they are executing of the titration procedure during the classes; 2- verify if there are differences between students as long as the evolution of a performance in concerned and investigate the factors (previous knowledge, general knowledge of chemistry, motivation, gender or subclass) which could elicit these differences. To reach these goals, a longitudinal study was held about the evolution of the performance of the students of the titration procedure in time (4 weeks). According to the analysis of the footage done for the research during the classes where the students were learning the procedure, it was built a scale for measuring of the performance of the students using the Rasch model. The longitudinal analysis of the skill was held using the multilevel modeling for change. The model obtained tells that the general knowledge of chemistry, the gender and the motivation affect the initial performance of the students and that there is no difference between the students as long as the changing rate is concerned that could be explained by these. The rate of growth of the skill was relatively low in the researched period. The scale seems valid and can be used in accessing the skill in the teaching environment. The time dedicated to the teaching and learning of the procedure seems to be insufficient to develop the expertise of the students in this area and this result may have implications in the curriculum of the technical courses